Implementation of Child Device Supervision Through Google Family Link: A Study of Families Using Google Family Link in Sukarami District, Palembang - Sawalika, Fella Mawaddah; Fatmariza; Wirda Nengsih; Eka Asih Febriani (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to analyze the implementation of parental supervision through Google Family Link, examine children’s responses to technology-assisted digital parenting, and identify the supporting and inhibiting factors affecting its implementation among families in Sukarami District, Palembang. Responding to growing concerns about children’s smartphone use, excessive screen time, digital addiction, and exposure to inappropriate online content, this study employed a qualitative case study design. Data were collected through non-participant observation, semi-structured interviews with parents, children, and other family members, and documentation. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings show that Google Family Link was implemented through screen-time management, application approval and restriction, activity monitoring, location tracking, and remote device control. Children’s responses varied from initial resistance to gradual acceptance as parents explained the purpose of digital supervision and involved them in establishing family digital rules. The study also found that parents’ digital literacy, family communication, consistency, and application usability supported effective implementation, whereas children’s resistance, technical limitations, unstable connectivity, and parents’ occupational demands constrained supervision. These findings indicate that Google Family Link functions not merely as a parental control application but as a social medium through which parents construct digital discipline, strengthen supervision, and foster responsible gadget use. However, the qualitative and context-specific design limits generalization; future studies should examine long-term outcomes across broader family, cultural, and socioeconomic settings.